Diatoms from the Colombian and Peruvian Amazon: the Genera Encyonema, Encyonopsis and Gomphonema (Cymbellales: Bacillariophyceae) - A. Vouilloud, Amelia (Universidad de Costa Rica, 2010)
Diatoms from the Colombian and Peruvian Amazon: the Genera Encyonema, Encyonopsis and Gomphonema (Cymbellales, Bacillariophyceae). The diatom flora of the Colombian and Peruvian Amazon is far less studied than the flora of the Brazilian sector of the basin. Here we present results related to the genera Encyonema, Encyonopsis and Gomphonema. Plankton and periphyton samples were collected in lotic and lentic waterbodies from the Amazonian-Andean region, the Amazon River, Japurá River and Porvenir River basins during 1993, 1994, 2001 and 2003. At each sampling station pH, temperature, water transparency and conductivity were registered. Samples were analyzed with phase contrast microscope (LM) and scanning electron microscope (SEM). Ten taxa are new records for the area; Encyonema for the Peruvian and Colombian Amazon and Encyonopsis for the Colombian Sector. Encyonema neogracile var. tenuipunctatum, E. vulgare, Encyonopsis frequentis, Gomphonema augur var. sphaerophorum and G. contraturris are recorded for the first time in Colombia; Encyonema venezolanum and G. neoapiculatum in Colombia and Peru and the latter also for Amazonia. E. angustecapitatum was mentioned in Colombia before at a pond located at 3000m asl. We describe a new species from Porvenir River, Amazonas, Colombia: Encyonema amazonianum.